TWEAK progress in dermatology: A review - Pramisha Kharel; Chen Jia; Kamal Raj Dhital; Pukar Chapagain; Sabita Aryal (Indian Journal of Dermatology, 2023)
Tumour necrosis factor (TNF)-like weak inducer of apoptosis (TWEAK) is a member of the TNF superfamily (TNFSF). It acts through its receptor fibroblast growth factor-inducible 14 (Fn14). Studies have indicated that TWEAK/Fn14 pathway activation controls multiple cellular responses, including proliferation, angiogenesis and induction of inflammatory cytokines. TWEAK/Fn14 is manifested in many tissues of our body and most importantly in the skin causing inflammation and many autoimmune and neoplastic cutaneous disorders. Evidence suggests that the TWEAK/Fn14 axis, the downstream signalling pathway and its inflammatory molecular expressions are involved in the pathogenesis of many cutaneous disorders such as psoriasis, atopic dermatitis (AD) vitiligo and melanoma. So, this literature review describes a brief introduction of TWEAK and TWEAK/Fn14 pathway and summarises the case-series and open-label studies performed in the field of dermatology and its potential therapeutic benefit.